Attack of the mutant - Stine, R. L. (New York : Scholastic, 1994)
Realizing that he has become lost in a strange part of town, Skipper Matthews, a ravenous comic book collector whose favorite character is an evil super-villain, discovers a building just like the secret headquarters of his idol.
"An Apple paperback."
370
510
Accelerated Reader AR
Keywords: Adventure stories; Adventure and adventurers -- Fiction; Horror stories